2019
DOI: 10.3390/ma12132212
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Abrasive Wear Resistance of Various Alloy Hardfacings for Application on Heavy-Duty Chipper Tools in Forestry Shredding and Mulching Operations

Abstract: Five different alloy hardfacings on 16MnCr5 grade low-carbon ferritic–pearlitic steel were investigated in terms of their abrasive wear resistance in laboratory testing conditions. The selected hardfacing materials, namely “E520 RB”, “RD 571”, “LNM 420FM”, “E DUR 600”, and “Weartrode 62”, were individually deposited onto plain ground-finish surfaces of 10 mm thick steel plate samples. The studied hardfacings were fabricated using several different welding methods and process parameters proposed by their indust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…There are a number of ways to mitigate problems connected with abrasive and other types of severe wear. Arc weld surfacing [ 8 , 9 , 10 , 11 ] is an effective method to reduce wear losses. Wear resistant materials may be also used to produce the entire working unit [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of ways to mitigate problems connected with abrasive and other types of severe wear. Arc weld surfacing [ 8 , 9 , 10 , 11 ] is an effective method to reduce wear losses. Wear resistant materials may be also used to produce the entire working unit [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cracks themselves do not significantly affect particle wear resistance, but can initiate fracture under static or dynamic stress. An unsuitable particle shape can cause the matrix to peel off at high loads [Choteborsky 2009] [Jahaveri 2018]. When welding by the TIG method, cracks in the bilayer cladding occurred in low to negligible amounts, as well as their size.…”
Section: Resultsmentioning
confidence: 99%
“…• the process of injecting the abrasive into the surface, where hardness is the decisive factor; • surface disruption process, where interatomic bonds and the strength of the bond between the structural components at the grain boundaries play a decisive role. Typical situations that occur during abrasive wear can be divided into: [Choteborsky 2009] Ideally, micro-scoring, the passage of a single abrasive particle does not result in any separation of material from the surface. The material is continuously moved to the sides, forming peaks adjacent to the already formed groove (Figure 3a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on comparison of all results from respective tests it can be observed that the B1 deposit is based on the structure analysis, hardness, adhesive wear, mechanical properties, rolling fatigue and residual stress the best suited clad layer. Based on the performed experimental work, in order to assess the suitability of the clad surfacing layers it is necessary to consider not only the mechanical properties of clad layers, but mainly the mutual relation between them, while considering also the tribological properties of clad layers for specific conditions of their wear in operation [37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%